2019
DOI: 10.1016/j.anireprosci.2019.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic and head morphometric characterisation of spermatozoa from the Brown Caiman (Caiman crocodilus fuscus)

Abstract: Kinematic and head morphometric characterisation of spermatozoa from the Brown Caiman (Caiman crocodilus fuscus)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 57 publications
0
18
0
2
Order By: Relevance
“…The multivariate approach of PCs and cluster analysis conducted for several species underscores that ejaculates are nevertheless heterogeneous in that they contain spermatozoa with different motility and kinematic patterns [ 17 , 22 , 31 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. In the present study, we identified four different sperm SPs described from three PCs that represented velocity, progressiveness, and cell undulatory movement.…”
Section: Discussionmentioning
confidence: 99%
“…The multivariate approach of PCs and cluster analysis conducted for several species underscores that ejaculates are nevertheless heterogeneous in that they contain spermatozoa with different motility and kinematic patterns [ 17 , 22 , 31 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. In the present study, we identified four different sperm SPs described from three PCs that represented velocity, progressiveness, and cell undulatory movement.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in sperm morphometry have been described between various related species (Soler et al, 2014b;Cucho et al, 2016;Valverde et al, 2019c), subspecies (Beletti et al, 2005) and breeds (Saravia et al, 2007;Valverde et al, 2016) (Table 2). Extrinsic factors may include those which influence the environment of the donor (Immler et al, 2010;Yániz et al, 2015).…”
Section: Morphometrymentioning
confidence: 96%
“…Semen collection has been performed post-mortem in the crocodile [10]. Interest in the development of assisted breeding technology of captive animals [11] has led to a refinement of semen collection protocols and characterization of sperm variables [12][13][14][15]. A common method of semen collection in wildlife is electroejaculation but this approach is highly stressful for crocodiles and induces urine contamination [13].…”
Section: Introductionmentioning
confidence: 99%
“…Characterization of sperm subpopulations has also received attention in fishes [37][38][39]. A previous study in the brown caiman (Caiman crocodilus fuscus) has revealed that kinematic sperm subpopulations can also be identified in this species [15].…”
Section: Introductionmentioning
confidence: 99%